Alticola tuvinicus Ognev 1950 ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
58. Tuva Mountain Vole Alticola tuvinicus French: Campagnol de Touva / German: Tuwa-Gebirgswiihimaus / Spanish: Topillo de montana de Tuva Other common names: Tuva Silver Vole Taxonomy. Alticola tuvinicus Ognev, 1950, vicinity of town Kyzyl, Tuvan Republic (S Siberia), Russia. Alticola tuvinicus was frequently synonymized with A. argentatus or A. roylei, and A. olchonensis was treated as a subspecies of A. tuvinicus. Monotypic. Distribution. S Russia (Khakassia and Tuva) and NW Mongolia (Mongol Altai); isolated population around Lake Khuvsgul in N Mongolia. Descriptive notes. Head—body 99-125 mm, tail 36-49 mm; weight 27-5-54-5 g. The Tuva Mountain Vole is similar in size and body proportion to the Silver Mountain Vole (A. argentatus). Tail is moderately long, 34-42% of head-body length, thick, well-haired, and tufted. Pelageis soft and long, gray or gray-brown dorsally, cream below, frequently heavily washed buff. Tail is clearly bicolored. Skull is strongly built but shallow, much like in the Mongolian ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 306, DOI: 10.5281/zenodo.6707142 ...